The ancient Maya marketplace : the archaeology of transient space / edited by Eleanor M. King. - King, Eleanor (The University of Arizona Press, 2015)
"The Ancient Maya Marketplace, edited by Eleanor M. King, reviews the debate on prehispanic Maya markets. The volume's contributors challenge the model of a non-commercialized Maya economy and offer compelling new evidence for the existence and identification of ancient marketplaces among the Maya"--Provided by publisher.